Introduzione (TEST Ticontre. Theory Text Translation, 2020)
This introduction presents the articles which are part of the monographic section and outlines the literary field of Italian periodicals from the late 1970s onwards.
Keywords: Riviste di poesia; poesia italiana contemporanea